Expression of opg, rank, and rankl proteins in tooth repair processes after immediate and delayed tooth - Manfrin, Thaís Mara [UNESP]; Poi, Wilson Roberto [UNESP]; Okamoto, Roberta [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Koogi [UNESP]; Saito, Célia Tomiko [UNESP]; Hamanaka, Elizane Ferreira [UNESP]; Martins, Christine Men [UNESP] (Wolters Kluwer, 2013)
This study evaluated the immunohistochemical expression of OPG, RANK, and RANKL proteins in the repair after immediate and delayed replantation of rat teeth. Fifty-six Wistar rats (Rattus norvegicus albinus) had their maxillary right lateral incisor extracted and then replanted, according to the following conditions: group I (control; n = 8), teeth were not extracted; group II (n = 16), immediate replantation; group III (n = 16), delayed replantation without treatment; and group IV (n = 16), delayed replantation after root surface treatment (periodontal ligament removal and immersion in 2% acidulated-phosphate sodium fluoride) and calcium hydroxide intracanal dressing. Rats in group I were euthanized on the first day of the experiment, while the animals in the other groups were euthanized 10 and 60 days after replantation (n = 8/period). Hematoxylin and eosin-stained sections were obtained for histological analysis. The immunohistochemical analysis revealed expression of OPG and RANKL proteins in all groups and both postreplantation times, except for group II at 60 days. In the experimental groups, RANK expression was observed only at 10 days. In conclusion, there was strong immunostaining for the OPG-RANK-RANKL system at the earlier postreplantation time, suggesting a more effective participation of these proteins at the start of the healing process, as their expression decreased at 60 days. Copyright © 2013 by Mutaz B. Habal, MD.
Keywords: Immunohistochemistry; osteoprotegerin; RANK ligand; tooth replantation